Single Intramuscular-dose Toxicity of Samgihwalryeok-Pharmacopuncture in Sprague-Dawley Rats - Sung-Chul Kim; Seong-Hun Ahn (Korean Pharmacopuncture Institute, 2014)
Objectives:This study was performed to examine the single-dose toxicity of Samgihwalryeok pharmacopuncture. Methods:Forty six-week-old Sprague-Dawley (SD) rats were divided into four groups of 10 rats each; each group was then sub-divided into two smaller groups, one of five males and the other of five females. Group 1 (G1, control) received 1.0 mL of normal saline solution, while group 2 (G2, low-dose group), group 3 (G3, mid-does group, and group 4 (G4, high-dose group) received 0.1, 0.5, and 1.0 mL of Samgihwalryeok pharmacopuncture, respectively. Results:No mortalities or clinical signs were observed in the four groups. Also, no significant changes in body weights were observed among the group, and no significant differences in hematology/biochemistry, necropsy, or histopathology results were noted. Conclusion:The above findings suggest that treatment with Samgihwalryeok pharmacopuncture is relatively safe. Further studies on this subject are needed.